Actors, Spaces, and the Politics of Knowledge in Education Governance? A Review of The Rise of Knowledge Brokers in Global Education Governance - Fitrah, Muh. (Nordic Journal of Comparative and International Education (NJCIE), 2025)
This review critically examines The Rise of Knowledge Brokers in Global Education Governance, edited by Chanwoong Baek and Gita Steiner-Khamsi, which marks a paradigmatic shift from policy transfer toward epistemic governance in global education. The book reveals how knowledge brokers, including actors, institutions, and networks, not only transmit knowledge but also shape legitimacy, norms, and the direction of international education policy. Through a reflective reading of its conceptual and empirical contributions, this review highlights three central dimensions: actors, spaces, and the politics of knowledge. These dimensions help explain how learning outcomes are constructed, negotiated, and socially legitimized. The analysis demonstrates that the circulation of global knowledge occurs within asymmetrical epistemic power relations between the Global North and the Global South. By advancing the notions of knowledge equity and epistemic justice, Baek and Steiner-Khamsi propose a reflective framework for more equitable knowledge governance. This review underscores the book’s theoretical and practical contribution to understanding the relationship between knowledge and power, and it emphasizes the urgency of strengthening local knowledge brokers in Southeast Asia, particularly Indonesia, as a concrete expression of epistemic justice in education policy.